2004
DOI: 10.1126/science.1098704
|View full text |Cite
|
Sign up to set email alerts
|

More Intense, More Frequent, and Longer Lasting Heat Waves in the 21st Century

Abstract: U-230 Th ages are derived as described in (14). See (34) for a review of 230 Th dating in magmatic systems. The reported ages are taken to be those of crystallization because of the relatively tight packing of ions within allanite and the tetravalent charge of Th [compare (35)]. Reequilibration of Th during magmatic residence will be insignificant: Based on the predictive model of Fortier and Giletti (36), Th diffusion would only affect ϳ2 m in allanite over a period of 100,000 years at the highest reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

63
2,449
2
33

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 3,495 publications
(2,547 citation statements)
references
References 14 publications
63
2,449
2
33
Order By: Relevance
“…This is in agreement with earlier studies connecting blocking to an increase in colocated summer HWs, which is found to be mainly driven by increased radiative forcing at the location of the block (e.g., Meehl & Tebaldi, 2004; Pfahl & Wernli, 2012; Sousa et al, 2018). However, our results also show anticorrelation of blocking with HWs in southern Europe for most seasons and regions.…”
Section: Resultssupporting
confidence: 93%
“…This is in agreement with earlier studies connecting blocking to an increase in colocated summer HWs, which is found to be mainly driven by increased radiative forcing at the location of the block (e.g., Meehl & Tebaldi, 2004; Pfahl & Wernli, 2012; Sousa et al, 2018). However, our results also show anticorrelation of blocking with HWs in southern Europe for most seasons and regions.…”
Section: Resultssupporting
confidence: 93%
“…Many global circulation models predict that temperate areas will become warmer and drier worldwide (Cao and Woodward 1998) with more extreme events such as severe heat waves and droughts (Easterling et al 2000;Meehl et al 2000), especially in Europe (Schär et al 2004). Such an increase in variability would strongly increase the occurrence of heat waves and drought (Meehl and Tebaldi 2004). It was previously demonstrated that this increase in temperature variability is clearly related to the feedbacks between the land surface and the atmosphere (Seneviratne et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, increasing attention has been paid to warm extremes [6][7][8][9][10] , which are expected to become more frequent, longer and more severe 11 . Europe emerges as an especially responsive area to temperature rise, particularly during the warm season 12 .…”
mentioning
confidence: 99%